Hank the Cowdog: The Big Question - Book 60 - Erickson, John R. 1943-; Holmes, Gerald L. (Perryton, TX : Maverick Books, 2012)
It's the day before Christmas, and Loper and Sally May have left Slim to manage the ranch while they go off to visit relatives for the holidays. But, a storm blows in and the electric fence separating a herd of steers from the highway shorts out. Now it's up to Slim, Viola and the ranch's Security Division to jump into action!
Keywords: Hank the Cowdog (Fictitious character) -- Juvenile fiction; Dogs -- Juvenile fiction; Ranch life -- Juvenile fiction -- Texas; Hank the Cowdog (Fictitious character) -- Fiction; Dogs -- Fiction; Ranch life -- Fiction -- Texas